2021
DOI: 10.3390/w13182567
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Trends in River Flow, Suspended Sediment Load, and Soil/Gully Erosion in the South of the Boreal Forest Zone of European Russia: The Vyatka River Basin

Abstract: Recent decades in the north of the East European Plain have been characterized by significant changes in climate and land use/cover, especially after the collapse of the USSR in 1991. At the same time, the hydrological consequences of these changes, especially changes in erosion processes and river sediment load, have been studied insufficiently. This paper partially covers this existing knowledge gap using the example of the Vyatka River basin. Draining an area of 129,000 km2, the Vyatka River is among the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the basin of the Vyatka River, one of the largest rivers in the boreal forest zone of the East European Plain (Russia), the river's suspended sediment load has decreased by almost 40% over the past 60 years due to a nearly 47% reduction in the area of cultivated land in its basin (Gusarov et al, 2021). Based on field, hydrological and modelled data, it was concluded that a reduction in surface runoff during the snowmelt period, an increase in the proportion of arable land under perennial grasses, and a decrease in the area of cultivated land, are key factors in reducing soil loss in river basins within the forest, forest steppe and steppe zones of the East European Plain (Mal'tsev et al, 2019;Gusarov, 2019).…”
Section: Sediment Fluxesmentioning
confidence: 99%
“…In the basin of the Vyatka River, one of the largest rivers in the boreal forest zone of the East European Plain (Russia), the river's suspended sediment load has decreased by almost 40% over the past 60 years due to a nearly 47% reduction in the area of cultivated land in its basin (Gusarov et al, 2021). Based on field, hydrological and modelled data, it was concluded that a reduction in surface runoff during the snowmelt period, an increase in the proportion of arable land under perennial grasses, and a decrease in the area of cultivated land, are key factors in reducing soil loss in river basins within the forest, forest steppe and steppe zones of the East European Plain (Mal'tsev et al, 2019;Gusarov, 2019).…”
Section: Sediment Fluxesmentioning
confidence: 99%
“…The recent decades in the north of the East European Plain have been characterized by Gusarov et al [22] with notable shifts in climate and land cover in the Vyatka River basin. Török et al [23] used the most popular empirical model's application range.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was due to increased economic activity within the watersheds, as well as significant climate change. During two or three centuries of the intensive development of watersheds for agricultural needs, the rivers have become heavily silted, although, after the collapse of the USSR in 1991, a significant decrease in the intensity of erosion and river runoff of suspended sediments was noted in the forest steppe zone of European Russia [62]. Under the conditions of the active intensification of soil erosion in watersheds, the main part of the floodplain-although it is regularly flooded with water and grows due to the vertical accumulation of sediments-is nevertheless not eroded and is not renewed by a concentrated channel flow of water.…”
Section: Introductionmentioning
confidence: 99%